A comparative analysis of progestin-primed ovarian stimulation versus GnRH antagonists protocols pertaining to stimulation parameters and embryological outcomes in patients with endometrioma - Boynukalin, Fazilet Kubra; Tohma, Yusuf Aytaç; Gultomruk, Meral; Yarkiner, Zalihe; Akkaya, Ceren Melisa; Ozkavukcu, Sinan; Bahceci, Mustafa; Bozdağ, Gürkan (Frontiers in Endocrinology, 2025)
Research questionDo embryo parameters and live birth rates differ between patients with endometrioma undergoing a freeze-all strategy using either GnRH antagonists or progestin-primed ovarian stimulation (PPOS)?DesignThis retrospective cohort study was conducted at Bahceci Health Group from January 2021 to January 2023. Inclusion criteria were females aged 20–40 with confirmed endometriosis, using either GnRH antagonists or PPOS ovarian stimulation, and opting for freezing all embryos without fresh embryo transfer (ET). A total of 543 patients were analyzed, with the primary outcome being usable embryos at cleavage stage and secondary outcomes including distribution of embryo quality, clinical pregnancy, and live birth rate.ResultsFor the GnRH antagonist arm, the median (25th-75th percentiles) total gonadotropin dose required during stimulation was significantly higher (2725 [2100–3587.5] vs. 2400 [2050–3075] IU, p = 0.001) and duration was longer (11 [10–12] vs. 10 [9–11] days, p = 0.01), although number of mature oocytes and maturation and fertilization rates were similar in both arms. However, the linear regression analysis revealed that the number of usable day-three embryos was higher with the PPOS protocol than with the GnRH antagonist protocol (OR: 0.890, CI 95%: 0.226 – 1.554, p= 0.009). Particularly in patients that had undergone FET, the respective live birth rates were 50.0% and 54.6% in GnRH antagonist and PPOS arms, respectively, without any statistical significance (p= 0.365).ConclusionIn patients with endometrioma, the PPOS protocol over GnRH antagonists might potentially enhance the quantity of usable cleavage-stage embryos while showing no significant impact on the number of collected oocytes.